Investigation of rheological properties of aged polymer modified binders - Yalçın, Erkut (My University, 2024)
Bituminous pavement layers used in road flexible superstructure are the top layer that is directly exposed to the effects of traffic and the environment and therefore must be very robust in terms of mechanical properties. To enhance the resistance of pavements against traffic loads and permanent deformations, Styrene Butadiene-Styrene (SBS) polymer additive is generally preffered. The high demand for SBS often presents challenges in obtaining it when needed, leading to a consideration of alternative additives. In this study, three different polymers, namely 701, 611, and SBS, were compared to assess their effectiveness as modifiers for bituminous materials. Modified bitumens were prepared using SBS, 701 and 611 polymers prepared under specified conditions. The modified binders were subjected to long and short term ageing. For both pure and modified binders, the Superpave binder (dynamic shear rheometer) test was conducted. Consequently, these binders improved the performance of the pure binder when the Superpave binder test findings of the four distinct binders employed in the study were analyzed.
Keywords: SBS; Aging; Rheology; Elastomer; Modified asphalt